LEXICAL DIFFERENCES ON WEST SUMBAWA REGIONAL DIALECT USED BY THE MEMBERS OF DORMITORY AT JALAN KADAKA NUMBER NUMBER 17 MALANG - SARASWATI, PUTRI AYU (Jurnal Ilmiah Mahasiswa FIB, 2014)
Key Words: Sociolinguistics, regional dialect, lexical differences, West Sumbawalanguage, West Sumbawa dormitory.Indonesia has many local languages. There language diversity found in each region in Indonesia, and called regional dialect. Dialect is language spoken in particular areas. This research aims at find out the lexical differences between Taliwang and Seteluk dialects used by the members of West Sumbawa dormitory at jalan Kadaka number 17 Malang. Further the researcher also investigates the meaning of those dialects.In this research, the researcher used qualitative approach. The researcher did anobservation, interview, note taking, and giving questionnaire. The researcher took the participants from West Sumbawa dormitory as the representation of West Sumbawanesse.The finding reveals thirty one lexical differences found in Taliwang and Seteluk dialects. The differences of Taliwang and Seteluk dialects happen because they come from different region of West Sumbawa. Thus these differences are perceived as dialect.In conclusion, differences in lexical of dialect may happen in different region andgeographical areas. The researcher hopes that this research may help the next researchers to develop their researches, further the next researchers can take another example of regional dialect to discuss.